2016
DOI: 10.1073/pnas.1602244113
|View full text |Cite
|
Sign up to set email alerts
|

Mass-tag labeling reveals site-specific and endogenous levels of protein S-fatty acylation

Abstract: Fatty acylation of cysteine residues provides spatial and temporal control of protein function in cells and regulates important biological pathways in eukaryotes. Although recent methods have improved the detection and proteomic analysis of cysteine fatty (S-fatty) acylated proteins, understanding how specific sites and quantitative levels of this posttranslational modification modulate cellular pathways are still challenging. To analyze the endogenous levels of protein S-fatty acylation in cells, we developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
210
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 156 publications
(225 citation statements)
references
References 37 publications
14
210
1
Order By: Relevance
“…Notably, peptides bearing palmitate on C72 were detected with a higher intensity in MS1 and higher confidence/score than peptides bearing palmitate on C71 (Figure 5C, SI Figure S25). These peptides are expected to have similar properties and should have similar solubility and fragmentation behaviors, which suggests that S-palmitoylation of IFITM3 at C72 is more prevalent that S-palmitoylation at C71, consistent with our previous indirect studies using alk-16 and APE 30 . Peptide ASTAKC(+palm)LNIW containing C105 was also identified in the sample with lower confidence (SI Figure 26 and SI Table 8).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Notably, peptides bearing palmitate on C72 were detected with a higher intensity in MS1 and higher confidence/score than peptides bearing palmitate on C71 (Figure 5C, SI Figure S25). These peptides are expected to have similar properties and should have similar solubility and fragmentation behaviors, which suggests that S-palmitoylation of IFITM3 at C72 is more prevalent that S-palmitoylation at C71, consistent with our previous indirect studies using alk-16 and APE 30 . Peptide ASTAKC(+palm)LNIW containing C105 was also identified in the sample with lower confidence (SI Figure 26 and SI Table 8).…”
Section: Resultssupporting
confidence: 86%
“…10,48 Our recent analysis of IFITM3 S-fatty-acylation by acyl-PEG exchange (APE) and alk-16 labeling revealed that C72A was the major site of S-fatty-acylation. 30 Since trypsin digest of IFITM3 results in large hydrophobic peptides (>29 amino acids), it appeared advantageous to digest IFITM3 with chymotrypsin, yielding 8–10 amino acid long peptides (SI Figure 18). Due to the predicted hydrophobicity of the lipidated peptides, we first performed preliminary experiments to test whether synthetic S-palmitoylated peptides could be detected by LC-MS/MS.…”
Section: Resultsmentioning
confidence: 99%
“…To measure endogenous Hras S-fatty-acylation levels during oxidative stress, we utilized an S-acyl-PEGylation exchange (APE) protocol developed by our laboratory (Supplementary Fig. 13a) 35 . The APE protocol is based on the acyl-biotin exchange protocol 36 , which caps free Cys residues and employs NH 2 OH to cleave thioesters for subsequent modification of thiols with PEG-maleimide reagents to induce a mass shift that is readily detectable by western blot (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work in vitro suggests that although this alteration of IFITM3 decreases antiviral activity against influenza virus, its activity against retroviruses is increased (29), thus revealing a potential selective advantage for the SNP that may explain its high prevalence in certain human populations (177). Additionally, given that IFITM3 antiviral activity is highly regulated by at least four posttranslational modifications, polymorphisms in factors that install or remove these modifications and impact influenza virus susceptibility may be uncovered in the future (22–24, 117, 172). …”
Section: Influenza Virusmentioning
confidence: 99%